Is body mass index associated with patellofemoral pain and patellofemoral osteoarthritis? A systematic review and meta-regression and analysis. Issue 10 (7th December 2016) - Hart, Harvi F; Barton, Christian J; Khan, Karim M; Riel, Henrik; Crossley, Kay M
Abstract : Background: Patellofemoral pain (PFP) occurs frequently, and may be related to patellofemoral osteoarthritis (PFOA). Obesity is associated with increased risk of knee OA. This systematic review involves a meta-regression and analysis to determine the relationship between body mass index (BMI) and PFP and PFOA, and to determine the link between BMI and interventional outcomes. Methods: We searched seven electronic databases and reference lists of relevant papers and systematic reviews, for cross-sectional, prospective, human-based observational and interventional studies reporting BMI in individuals with PFP or PFOA compared to healthy controls. Two independent reviewers appraised methodological quality (epidemiological appraisal instrument). Where possible, data from prospective studies were pooled to conduct meta-regression and case–control, and intervention studies to conduct meta-analysis using the following categories: adolescents with PFP, adults with PFP and PFOA. Results: 52 studies were included. We found greater BMI in adults with PFP (standardised mean difference: 0.24, 95% CI 0.12 to 0.36) and PFOA (0.73, 0.46 to 0.99) compared to healthy controls, but not in adolescents with PFP (−0.19, −0.56 to 0.18). We also observed statistical trends (p<0.10) towards higher BMI being a predictor for development of PFP in adults (0.34, −0.04 to 0.71). No significant link between BMI and intervention outcomes in adults with PFP was identified. Conclusions: Higher BMI is present in PFP and PFOA, but not in adolescents with PFP. PROSPERO registration number: CRD42015024812.